The Influence of Plyometric Training on Increasing the Shooting Accuracy: Pengaruh Latihan pliometrik pada Peningkatan Akurasi Shooting - Angga Nugraha; Iskandar, Dedi (Champions: Education Journal of Sport, Health, and Recreation, 2024)
Football is a sport that requires mastery of fundamental techniques, including accurate shooting, to score goals and win matches. Observations at SSB Tesa FC Kutaraja revealed that many players struggle with shooting techniques, highlighting the need for an effective training method to address this issue. This study emphasizes the importance of improving shooting quality among SSB Tesa FC Kutaraja players, given that shooting is a critical skill in football for scoring goals and securing victories. The findings indicate that plyometric training significantly enhances players' shooting accuracy. The Wilcoxon test carried out produced a significance value (2-tailed) of 0.000, which indicated a significant increase in shooting accuracy after plyometric training. This approach has significantly improved shooting skills, making it a valuable addition to football training programs. The contribution of this research lies in reinforcing the theoretical foundation on the effectiveness of plyometric training in skill development and providing coaches with guidance for designing more effective training programs. Future research is encouraged to explore the combined effects of plyometric training with other methods to further enhance football skills.